Factors affecting task group selection - Legkauskas, Visvaldas (Psichologija, 2002)
Social Identity Theory and Optimal Distinctiveness Theory are two main theoretical models relevant for explanation of task group selection and identification with task groups. It is argued that while having some validity, both of those theories ignore importance of the need to be cared about manifested by striving to contribute, as a central motivational factor in identification with task groups. To test this proposition, a study was conducted in which the author assessed relative importance of optimal distinctiveness, self-esteem, and contribution motives for choice of task groups. Subjects were 35 university students (19 women and 16 men, mean age 20 years), who had had experience in team sports. Subjects were presented with a description of competitive team sports situation, in which they had to choose groups depending on their distinctiveness, prestige, and possibility to contribute to the group results. Results indicate, that all three factors had an independent motivating value. Of the three, possibility to contribute to the group results was the most important factor, followed by group prestige, which was in turn followed by group distinctiveness.